Extensive metabolic disorders are present in APCmin tumorigenesis mice. (15th May 2016) - Liu, Zhenzhen; Xiao, Yi; Zhou, Zhengxiang; Mao, Xiaoxiao; Cai, Jinxing; Xiong, Lu; Liao, Chaonan; Huang, Fulian; Liu, Zehao; Ali Sheikh, Md Sayed; Plutzky, Jorge; Huang, He; et al.
Abstract: Wnt signaling plays essential role in mesenchymal stem cell (MSC) differentiation. Activation of Wnt signaling suppresses adipogenesis, but promotes osteogenesis in MSC. Adenomatous polyposis coli (APC) is a negative regulator of β-catenin and Wnt signaling activity. The mutation of APC gene leads to the activation of Wnt signaling and is responsible for tumorigenesis in APC min mouse; however, very few studies focused on its metabolic abnormalities. The present study reports a widespread metabolic disorder phenotype in APC min mice. The old APC min mice have decreased body weight and impaired adipogenesis, but severe hyperlipidemia, which mimic the phenotypes of Familial Adenomatous Polyposis (FAP), an inherited disease also caused by APC gene mutation in human. We found that the expression of lipid metabolism and free fat acids (FA) use genes in the white adipose tissue (WAT) of the APC min mice is much lower than those of control. The changed gene expression pattern may lead to the disability of circulatory lipid transportation and storage at WAT. Moreover, the APC min mice could not maintain the core body temperature in cold condition. PET–CT determination revealed that the BAT of APC min mice has significantly impaired ability to take up 18 FDG from the blood. Morphological studies identified that the brown adipocytes of APC min mice were filled with lipid droplets but fewer mitochondria. These results matched with the findings of impaired BAT function in APC min mice. Collectively, our study explores a new mechanism that explains abnormal metabolism in APC min mice and provides insights into studying the metabolic disorders of FAP patients. Highlights: Downregulated expression of FFA use genes in old APC min mice causes lean but elevated serum lipid level. APC min mice have impaired brown adipose tissue function. Increased gluconeogenesis in the liver may partially account for the hyperglycemia of the APC min mice.